Severe Maternal Morbidity among Women in the U. S. Military, 2003–2015 - Hall, Clinton; Romano, Celeste J.; Bukowinski, Anna T.; Gumbs, Gia R.; Dempsey, Kaitlyn N.; Poole, Aaron T.; Conlin, Ava Marie S.; Lamb, Shannon V. (American Journal of Perinatology, 2021)
Objective This study aimed to assess trends and correlates of severe maternal morbidity at delivery among active duty women in the U.S. military, all of whom are guaranteed health care and full employment.Study Design Linked military personnel and medical encounter data from the Department of Defense Birth and Infant Health Research program were used to identify a cohort of delivery hospitalizations among active duty military women from January 2003 through August 2015. Cases of severe maternal morbidity were identified by applying 21- and 20-condition algorithms (with and without blood transfusion) developed by the Centers for Disease Control and Prevention. Rates (per 10,000 delivery hospitalizations) were reported overall and by specific condition. Multivariable Poisson regression models estimated associations with demographic, clinical, and military characteristics.Results Overall, 187,063 hospitalizations for live births were included for analyses. The overall 21- and 20-condition severe maternal morbidity rates were 111.7 (n = 2089) and 37.4 (n = 699) per 10,000 delivery hospitalizations, respectively. The 21-condition rate increased by 184% from 2003 to 2015; the 20-condition rate increased by 40%. Compared with non-Hispanic White women, the adjusted 21-condition rate of severe maternal morbidity was higher for Hispanic (adjusted rate ratio [aRR] = 1.28, 95% confidence interval [CI]: 1.13–1.46), non-Hispanic Black (aRR = 1.34, 95% CI: 1.21–1.49), Asian/Pacific Islander (aRR = 1.35, 95% CI: 1.13–1.61), and American Indian/Alaska Native (aRR = 1.39, 95% CI: 1.06–1.82) women. Rates also varied by age, clinical factors, and deployment history.Conclusion Active duty U.S. military women experienced an increase in severe maternal morbidity from 2003 to 2015 that followed national trends, despite protective factors such as stable employment and universal health care. Similar to other populations, military women of color were at higher risk for severe maternal morbidity relative to non-Hispanic White military women. Continued surveillance and further investigation into maternal health outcomes are critical for identifying areas of improvement in the Military Health System.Key Points
Keywords: severe maternal morbidity; pregnancy complications; racial disparities; military